Receivables discounting in the enterprise accounting policy - I. Tralo (Економіка, управління та адміністрування)
The economic activity of an enterprise is carried out in accordance with the rules that are formed in the regulatory legislation and internal documents, such as: charter, accounting policy, risk management policy, contracts, regulations, orders, etc. In order to maximize the results of their activities, business entities are interested in developing the most rational enterprise management policy that will take into account the various options available to them to take advantage of the opportunities and benefits available. The presence of receivables in the assets of an enterprise indicates the expansion of production and sales of products. The reliability and timeliness of methods of receivables in the assets assessment in accounting should be based on current methods and take into account the probable risks of insolvency of counterparties . Therefore, the article focuses on changes that are taking place in accounting policies of the company due to the use of discounting as a method of estimating long-term receivables. On this basis, the characteristic directions of updating the accounting policy provisions were identified and the mechanism of their implementation. The proposed approach makes use of the benefits of the process of discounting long-term receivables and facilitates the transition of enterprises to a new stage of harmonization of the provisions of the national accounting system with international standards.